ОNE-YEAR CLINICAL EVALUATION OF THE CARIES-PREVENTIVE EFFECT OF GLASS-IONOMER SEALANT ON NEWLY ERUPTED FIRST PERMANENT MOLARS IN CHILDREN - Lilyana Shtereva; Mariana Dimitrova; Veselina Kondeva (Peytchinski Publishing, 2022)
Background: Dental sealant is a material that is applied to pits and fissures in order to prevent the occurrence of occlusal dental caries. The caries-prophylactic effect of sealants on a glass-ionomer basis has not been sufficiently studied, which motivates us to conduct our research. Purpose; To monitor the caries-preventive effect of a glass-ionomer-based sealant after silanization of the newly erupted first permanent molars in children aged 5-6 years. Materials and methods: We started the study with 78 healthy, newly erupted first permanent molars (silanized with Fuji triage, GC), the follow-up was performed at 3,6 and 12 months by visual method on the ICDAS II system, diagnostics under magnification using VistaCam Macro and modified Ryge criteria. After recoding the data obtained from monitoring the occlusal surfaces of the newly erupted first permanent molars, we performed a frequency analysis of the data depending on the absence or presence of caries. Results: In the group of 5-6-year-olds after the application of glass-ionomer-based sealant in the newly erupted first permanent molars, one year after application of the sealant, we assessedver 95% of the examined surfaces as healthy with all diagnostic methods that we used. Conclusion: Glass-ionomer cements used for silanization are the main tool of choice when it is impossible to control moisture, as is the case with newly erupted molars. Despite their significantly low retention, they provide an excellentaries-prophylactic effect.